1965
DOI: 10.1111/j.1365-2621.1965.tb00291.x
|View full text |Cite
|
Sign up to set email alerts
|

Proteolytic Action of Pepsin on Glutenin

Abstract: Pepsin rapidly decreases the viscosity of a glutenin dispersion having an acid reaction and rapidly increases -the amount of water-soluble fragments.The molecular weight of the solubilked fragments, estimated by the gel-filtration method, indicates that most of the fragments are large and have:molecular weights greater than 10,000.A comparison of data obtained by gel filtrtition and by determination of terminal amino acids in pepsin hydrolysates of glutenin indicates that cleavage of a few peptide bonds rapidl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1967
1967
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…However, free amino acid nitrogen was not detected until 12 h of hydrolysis, when free phenylalanine, leucine, valine, and tyrosine were present. Proteolysis of glutenin by pepsin was shown by Oka et al (1965) to rapidly decrease the viscosity of the dispersion and increase the water-soluble fraction. These workers suggested that these early changes were results of cleavage of a few F(O.Ol)l,ll = 9.65**; F(0.05)1,11 = lated boundary condition; a response of 1.00 was arbitrarily assigned t o force the factor back inside the boundary by a contraction.…”
Section: Resultsmentioning
confidence: 98%
“…However, free amino acid nitrogen was not detected until 12 h of hydrolysis, when free phenylalanine, leucine, valine, and tyrosine were present. Proteolysis of glutenin by pepsin was shown by Oka et al (1965) to rapidly decrease the viscosity of the dispersion and increase the water-soluble fraction. These workers suggested that these early changes were results of cleavage of a few F(O.Ol)l,ll = 9.65**; F(0.05)1,11 = lated boundary condition; a response of 1.00 was arbitrarily assigned t o force the factor back inside the boundary by a contraction.…”
Section: Resultsmentioning
confidence: 98%
“…Small amounts of proteases can have large effects on gluten physical properties. Oka et al. (1965) demonstrated that breakage of a few peptide bonds resulted in a rapid decrease in viscosity of glutenin dispersion.…”
Section: Introductionmentioning
confidence: 99%
“…Small amounts of proteases can have large effects on gluten physical properties. Oka et al (1965) demonstrated that breakage of a few peptide bonds resulted in a rapid decrease in viscosity of glutenin dispersion. Also, Redman (1971) reported evidence to support the hypothesis that gluten softening is the direct result of peptide bond scission catalyzed by proteases.…”
Section: Introductionmentioning
confidence: 99%
“…Small amounts of proteases can have a large effect on gluten physical properties. Oka et al. (1965) demonstrated that breakage of a few peptide bonds resulted in a rapid decrease in viscosity of glutenin dispersion.…”
Section: Introductionmentioning
confidence: 99%